2009
DOI: 10.1111/j.1745-4557.2009.00259.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Storage Temperature on Meat Quality of Muscle With Different Fiber Type Composition From Korean Native Cattle (Hanwoo)

Abstract: Three kinds of Hanwoo (Korean native cattle) muscles (Loin, strip loin and inside round) were obtained from a local farm and then divided into two storage temperatures (0 and 5C), respectively. In meat color, redness (a*) was significantly higher in 5C storage samples compared with 0C storage samples in all muscle samples after 7 days of storage. Loin had significantly lower purge loss than other muscle samples, whereas inside round was significantly higher in purge loss. Strip loin showed lower shear force va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 17 publications
1
9
1
Order By: Relevance
“…However, acceptability, juiciness, and flavor liking did not differ between the various postmortem aging periods [4], which contradicts the current findings as flavor liking and overall liking decreased with increasing aging period in the present findings. We believe the discrepancy in results between these two studies could again be related to postmortem storage temperature, as previous work has shown increased storage temperature (0 • C vs. 5.0-5.5 • C) of vacuum packaged beef can negatively affect shelf-life and palatability, especially when aging beef beyond 28 postmortem [19,20]. Colle et al [4] stored vacuum-packaged muscle sections at 0 • C, which is again lower than the current study.…”
Section: Consumer Sensorycontrasting
confidence: 71%
“…However, acceptability, juiciness, and flavor liking did not differ between the various postmortem aging periods [4], which contradicts the current findings as flavor liking and overall liking decreased with increasing aging period in the present findings. We believe the discrepancy in results between these two studies could again be related to postmortem storage temperature, as previous work has shown increased storage temperature (0 • C vs. 5.0-5.5 • C) of vacuum packaged beef can negatively affect shelf-life and palatability, especially when aging beef beyond 28 postmortem [19,20]. Colle et al [4] stored vacuum-packaged muscle sections at 0 • C, which is again lower than the current study.…”
Section: Consumer Sensorycontrasting
confidence: 71%
“…All findings suggest that dietary VA improved meat color. The lactic acid content in muscle after slaughter is reflected in pH, and acidity leads to denaturation of muscle protein, decrease of water retention, and whitening so as to damage meat quality ( Castellini et al., 2002 , Hur et al., 2009 ). Supplementing broiler diets with 5,000 IU/kg VA significantly decreased pH 45 min postmortem, consistent with the earlier work of Hong et al.…”
Section: Discussionmentioning
confidence: 99%
“…According to Hur et al (2009) , high pH was closely related to high water-holding capacity. LIM cattle had better water-holding capacity than that of other cattle breeds in the present study, this may be due to their higher pH values.…”
Section: Discussionmentioning
confidence: 99%
“…Lipid oxidation was a leading cause of quality deterioration in meat and meat products ( Hur et al, 2009 ). As Warren et al (2008) reported, this study also found that breed had an effect on lipid oxidation.…”
Section: Discussionmentioning
confidence: 99%